MOORCHEH KHORT HISTORICAL FORTRESS: THE ENTRY GATE OF IRAN’S ANCIENT CAPITAL - Reza Manouchehri, Mohammad; Jafari, Sousan (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Moorcheh Khort historical fortress is a much valued but lesser known historical site located on the Iranian Central Plateau. This article attempts to develop a model by utilizing an archeological and architectural research methodology framework with spatial analysis to study the interaction among existing spaces with consideration given to the outcomes of social changes, which have occurred throughout the various historical periods in Iran with a focus on local signiicance. Moorcheh Khort is used as the model in this study due to its historical signiicance as one of the largest clay construction complexes on the Iranian Central Plateau and its possession of unique architectural features characterized by the material used in its construction.